Modern weapons and military equipment for issue 3-2016 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Upgraded Indian M46 contenders to shoot it out in desert trials China gives DF-5As multiple warheads Raining down: Assessing the emergent ASBM threat Russia reveals new SU-30 SME „Flanker“ UralVagonZavod reveals T-90 MS details Airbornarmour Russian forces set for BTR-MDM Taking out the archer:NIFC-CA concept goes to sea Russian 6S21 RWS adopts modular approach Hypersonic hustle: Global efforts raise to satisfy need for speed Ukraine develops Mi-8 MSB-V upgrades Rafael begins DSWS deliveries to IAF North Korean rocket motor test increases ICBM credibility